FORMING MODELS OF CLASSIFICATION OF SOCIAL PROCESSES IN PUBLIC IN PUBLIC ADMINISTRATION: CONCEPTUAL-CATEGORICAL APPARATUS - Oleksenko , R; Voronkova , V. (Theory and Practice of Public Administration, 2020)
The actuality of the investigated problem is that the theory of classification of social processes in public administration is almost not examined and studied, while classification of social processes depends on efficiency and effectiveness of public administration and management. The main task of the article is to analyze the theory of classification of social processes in public administration, which is necessary for information support in the field of improving the quality of public administration and administration organization. The solving of problems of improving the quality of organization of public administration and administration is focused on the problem of programming the development of its system forming structures. The leading approach to research of the given problem is application of the system-hierarchical approach to formation of model of classification of social processes should be applied taking into consideration specific variety, in this case public administration. In the literature focused on the systems approach, this is called the general theoretical or special scientific approach. In the article the directions of improving the quality of public administration are found out, it is being focused on the task of programming the development of its system forming structures. The ontology of hierarchy of structure of social process is disclosed, it is realized in political sphere of life activity of society. The classification of social processes is formed, at the basis of which more complex, average and small scales of social processes which are presented in models by taxons of different levels, are important to use in administrative activity at all levels. There is a substantiated conceptual-categorical apparatus of formation of the model of classification of social processes in public administration, expressed by the concepts of taxon, autopoesis, and hierarchy. The research on formation of the model of classification of social processes in public administration and its conceptual-categorical apparatus are really valuable for managers of all levels, as it discloses an innovative approach to public administration, which is based on improving quality, its efficiency and effectiveness.